Indicadores antropométricos do estado nutricional entre idosas praticantes e não praticantes de exercício físico na zona norte de São José do Rio Preto-SP - Cachoni, Lilian [UNESP]; Baida, Luiz Carlos [UNESP]; Costa, Vera Mariza Henriques de Miranda [UNESP]; Oliveira, Maria Rita Marques de [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Although the regular practice of physical exercise for the maintenance of the nutritional state and quality of life is important, it is not a common habit among the elderly, especially those of the lower income social bracket. The objective was to characterize and compare according to social-economic conditions and anthropometric indexes of the nutritional state of the elderly who regularly practice and those who do not practice exercises, offered at no cost, in the Northern zone of São José do Rio Preto-SP. In this study, 110 elderly women participated, of which 60 (group P) exercised regularly and 50 did not (group NP). Group P participated in a special gym program, free of charge, for at least 2 years, 2 to 3 times a week, one hour a day. Group NP was recruited from the same location as Group P. The comparison between the groups of elderly women was proportionately distributed according to marital status, level of education, means of locomotion, results of body mass index (IMC), waist to hip ratio (RCQ) and calf circumference, using the chi-square test. Comparisons were also made of average age, per capita family income, individual income, IMC, arm and triceps skin fold measured by t-Test. Differences were not found in all the comparisons made. The variables that stood out were the IMC (overweight) and RCQ (risk of chronic diseases) results, which were above what was expected, and the high frequency of walking and riding buses for both groups of elderly women (about 60%). We came to the conclusion that the low-intensity exercise program evaluated made no difference in the nutritional profi le of the elderly who also used walking as a means of getting around.

Apesar da importância da prática regular de exercício físico para a manutenção do estado nutricional e da qualidade de vida, esse hábito é pouco frequente entre idosos, especialmente para as classes sociais menos favorecidas. O objetivo foi caracterizar e comparar, segundo a condição socioeconômica, os indicadores antropométricos do estado nutricional de idosas praticantes e não praticantes regulares de exercício físico em ambiente gratuito na zona norte de São José do Rio Preto-SP. Neste estudo, participaram 110 idosas, 60 praticantes regulares (grupo P) de exercício físico e 50 não praticantes (grupo NP). O grupo P participava de um programa de ginástica especial gratuito há pelo menos 2 anos, 2 a 3 vezes por semana, uma hora ao dia. O grupo NP foi recrutado na mesma região de residência do grupo P. Foram comparados entre os grupos: distribuição proporcional das idosas, segundo estado civil, grau de instrução, meios de locomoção, valores de índice de massa corporal (IMC), relação cintura quadril (RCQ) e circunferência da panturrilha, pelo teste de qui-quadrado. Foram ainda comparadas as médias de idade, renda familiar per capita, renda individual, IMC, circunferência do braço e prega cutânea do tríceps, pelo teste t. Não foram encontradas diferenças em todas as comparações realizadas. Destacaram-se, entre as variáveis, os valores acima do esperado para IMC (excesso de peso) e RCQ (risco de doenças crônicas) e elevada frequência do andar a pé e de ônibus para os dois grupos de idosas (aproximadamente 60%). Concluiu-se que o programa de exercício de baixa intensidade avaliado não resultou em diferença no perfi l nutricional de idosas que tinham também como meio de locomoção frequente o andar a pé.
Anthropometric indexes of the nutritional state of elderly women who practice and those who do not practice physical exercises in the northern region of the city of São José do Rio Preto-SP
Keywords: Elderly; Physical exercise; Anthropometry; Social condition; Public policies; Idoso; Estado nutricional; Avaliação nutricional; Autonomia